Infrared drying of sweet potato (Ipomoea batatas L.) slices - Doymaz, Ibrahim (SPRINGER INDIA, 2012)
The effect of different infrared power levels (104, 125, 146 and 167 W) on drying kinetics and rehydration ratio of sweet potato slices was investigated. It was observed that the power levels affected the drying time and rehydration ratio. The increase in infrared power level decreased the drying time. The experimental data obtained from drying study were fitted with Newton, Henderson and Pabis and Logarithmic models to evaluate the drying kinetics of the sweet potato slices. The fit quality of the proposed models was evaluated by using the determination of coefficient (R (2) ), mean relative percent error (P), reduced chi-square (chi (2) ) and root means square error (RMSE). Among the three drying models, the Logarithmic model gave a better fit over the other two models. Effective diffusivity varied from 1.31 x 10(-10) to 3.66 x 10(-10) m(2)/s and was significantly influenced by infrared power.
Keywords: Sweet potato; Infrared drying; Rehydration ratio; Effective diffusivity; REHYDRATION KINETICS; MOISTURE DIFFUSIVITY; ONION SLICES; LAYER; RADIATION; TEMPERATURE; MODELS; FRESH; COLOR; Food Science & Technology